The Cost Difference of Hospital Rates and Indonesia Case Base Grup (Ina CBGs) Rates of Inpatient with National Health Insurance Scheme at Private Hospital - Dhaniah El Fitri; Sri Sundari (Universitas Aisyah Pringsewu, 2023)
Background: Universal Health Coverage (UHC) stands for the ideal that everyone should have access to high-quality healthcare without facing financial hardship. Hospitals have an important role in the implementation of the referral system with the National HeaIth Insurance scheme. The porspektif payment system allows for difference between the Hospital rates and the INA CBGs rates. The difference in costs has the potential to cause benefits or losses for hospitals and plays an important role in supporting the sustainability of the hospitals. The challenges faced by private hospitals are different from those of government hospitals. Private hospitals must self-fund all costs incurred including investment costs and operating expenses This study aimed to evaluate the difference between hospital rate and INA-CBG’s rate, focus on inpatient with NHI scheme at a private hospital at Yogyakarta, identifying the cases that contributes to a common effect of cost difference and identifying the cost components that have the most impact to the dominant cost difference. Methods: We performed a retrospective quantitative research with secondary data analysis. Data was obtained from hospital billing of a Private Hospital type C at Yogyakarta , a referral hospital in Indonesia, at period of January– December 2021. The data involved of 4474 cases of inpatient with National Health Insurance Scheme. The analysis was carried out with Pareto analysis. Results : The difference between hospital rate and Ina CBGs rate of all case is 32,5 %. The pareto analysis results that there are some NHI inpatient cases contribute a common cost difference as 1389 (31% of total cases) as high cost case. These cases contribute 80 % of total cost difference. The cost components that have the most impact to the dominant cost difference are surgical prosedurs (26,1 %) and room and acomodation cost (19,7%). Conclusions: There are cost difference in which the hospital rate is higher than the Ina CBGs rate . There are 31 % of total cases as high cost cases, for the bulk of the cost difference. Surgical procedurs, room and acomodation cost are the cost components that have the most impact to the dominant cost differences. This study support the necessary for hospitals to evaluate the cost difference of hospital rate and Ina CBGs rate periodically for improving quality and cost efficiency at hospitals.